2014
DOI: 10.4161/onci.29179
|View full text |Cite
|
Sign up to set email alerts
|

Trial Watch

Abstract: Toll-like receptors (TLRs) are an evolutionarily conserved group of enzymatically inactive, single membrane-spanning proteins that recognize a wide panel of exogenous and endogenous danger signals. Besides constituting a crucial component of the innate immune response to bacterial and viral pathogens, TLRs appear to play a major role in anticancer immunosurveillance. In line with this notion, several natural and synthetic TLR ligands have been intensively investigated for their ability to boost tumor-targeting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(45 citation statements)
references
References 176 publications
0
45
0
Order By: Relevance
“…Nonetheless, HMGB1-deficient malignant cells exposed to ICD inducers fail to elicit adaptive immune responses upon inoculation into immunocompetent syngeneic mice, a defect that can be corrected by the co-administration of synthetic TLR4 ligands. [225][226][227][228] Together with the notion that Tlr4 ¡/-mice fail to perceive anthracycline-treated syngeneic cells as immunogenic, 41,229 this observation demonstrates the importance of the HMGB1-TLR4 signaling axis for ICD.…”
Section: Immunogenic Cell Death Signalingmentioning
confidence: 84%
“…Nonetheless, HMGB1-deficient malignant cells exposed to ICD inducers fail to elicit adaptive immune responses upon inoculation into immunocompetent syngeneic mice, a defect that can be corrected by the co-administration of synthetic TLR4 ligands. [225][226][227][228] Together with the notion that Tlr4 ¡/-mice fail to perceive anthracycline-treated syngeneic cells as immunogenic, 41,229 this observation demonstrates the importance of the HMGB1-TLR4 signaling axis for ICD.…”
Section: Immunogenic Cell Death Signalingmentioning
confidence: 84%
“…Our data suggest that this vaccine should be added to the list of TLR agonists to be tested in oncologic indications. 41 Expression of chemokines and ESL among CD4 T cells (black symbols) or among CD8 T cells (white symbols) is shown. ND: not detectable.…”
Section: Ccl9 May Attract Ccr1-expressing Macrophages or Dendritic Cementioning
confidence: 99%
“…Among this abundant literature, we found of especial interest the works of (1) Arulanandam and colleagues (Ottawa Hospital Research Institute, Ottawa, Canada), who discovered that a transcriptional modulator operating downstream of vascular endothelial growth factor receptors (VEGFRs) 208,209 suppresses Type I interferon (IFN) responses, 210 hence sensitizing the tumor vasculature to infection by oncolytic viruses, 211 and found that microtubule-destabilizing agents commonly employed in the clinic (e.g., paclitaxel) 212,213 synergize with oncolytic virotherapy by disrupting the translation of Type I IFN-coding mRNAs and by exacerbating the demise of cancer cells provoked by the cytopathic effect; 214 (2) Nishio and collaborators (Baylor College of Medicine, Houston, TX, US), who reported that an oncolytic adenovirus genetically engineered to express interleukin-15 (IL-15) and chemokine (C-C motif) ligand 5 (CCL5, also known as RANTES) improved the therapeutic potential of adoptively transferred T cells expressing a chimeric antigen receptor (CAR) 215,216 [218][219][220][221][222] a means to boost the replication (and hence the efficacy) of an oncolytic HSV-1 strain; 223 (4) Parrish and co-authors (St James's University Hospital, Leeds, UK), who discovered that an oncolytic reovirus enhances the capacity of the FDA-approved CD20-targeting monoclonal antibody rituximab 224,225 to stimulate antibody-dependent cellular cytotoxicity; 226 , who discovered that autonomous parvoviruses are endowed with a rather advantageous feature for the development of novel oncolytic virotherapies, namely, they neither trigger nor inhibit Type I IFN responses in normal and malignant cells; 236 (11) Zloza and coauthors (Rush University Medical Center, Chicago, IL, US), who suggested that the downregulation of leukocyte immunoglobulin-like receptor, subfamily B (with TM and ITIM domains), member 1 (LILRB1, also known as ILT2) in peripheral blood mononuclear cells may constitute a reliable biomarker of therapeutic responses to oncolytic virotherapy in cancer patients; 237 (12) Liikanen and colleagues (University of Helsinki, Helsinki, Finland), who propose that the circulating levels of the damage-associated molecular pattern high mobility group box 1 (HMGB1) [238][239][240][241] at baseline may constitute a robust prognostic factor as well as a predictive indicator of disease control up...…”
Section: Preclinical and Translational Advancesmentioning
confidence: 99%